2020
DOI: 10.5038/2577-509x.4.2.1051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pre-intervention IDI results from STEM and non-STEM undergraduate students

Abstract: The emphasis on intercultural competence is more prevalent in STEM (Science, Technology, Engineering and Mathematics) majors as the world shifts towards a more globalized economy. When entering higher education, students have differing levels of cultural interaction due to varying peer interaction, family experiences, international travel, and social media experiences. The Intercultural Development Inventory (IDI) has been used to develop an understanding of how students view others and the level of skills the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In contrast with Byram (1997Byram ( , 2000, who conceptualizes ICC as pertaining to communication across diverse linguistic and cultural worlds, the DMIS draws on concepts from cognitive psychology and constructivism to explain how individuals experience cultural difference and how their evolving perspective directs and constrains their interpretations of cultural events. This model, that has been extensively used for intercultural training in higher-education programs without specific focus on FL study (e.g., Jackson, 2017;Lucietto & Russell, 2020;Pedersen, 2017), provides a six-stage path to becoming interculturally competent, representing a valuable tool for FL instructors and researchers interested in ICC development.…”
Section: Icc: Definitions and Frameworkmentioning
confidence: 99%
“…In contrast with Byram (1997Byram ( , 2000, who conceptualizes ICC as pertaining to communication across diverse linguistic and cultural worlds, the DMIS draws on concepts from cognitive psychology and constructivism to explain how individuals experience cultural difference and how their evolving perspective directs and constrains their interpretations of cultural events. This model, that has been extensively used for intercultural training in higher-education programs without specific focus on FL study (e.g., Jackson, 2017;Lucietto & Russell, 2020;Pedersen, 2017), provides a six-stage path to becoming interculturally competent, representing a valuable tool for FL instructors and researchers interested in ICC development.…”
Section: Icc: Definitions and Frameworkmentioning
confidence: 99%
“…The IDI instrumentalizes the DMIS theory and is a valid and reliable intercultural development assessment (Wiley, 2016; Wiley, 2017). Paige et al (2003) argue that the IDI assesses intercultural competency and Lucietto and Russell (2020) assert that it is not subject to social desirability bias.…”
Section: Program Evaluation Methodsmentioning
confidence: 99%
“…The IDI was chosen as a program evaluation tool because it is a theory-based and developmental tool (Bennett, 1986(Bennett, , 1993Bennett and Bennett, 2004) used by many educational organizations to achieve US domestic diversity and inclusion goals (Bennett and Bennett, 2004;Hammer et al, 2003;Harvey, 2017;Paige et al, 2003;Lucietto and Russell, 2020). Harvey (2017) argues that the IDI is a useful tool to use in a developmental curriculum like the program evaluated here.…”
Section: Intercultural Development Inventorymentioning
confidence: 99%
“…Studies have revealed that working within a diverse work environment can be challenging for fresh graduates (Bahrami et al, 2023;Du & Kolmos, 2009;Rock et al, 2016). It has also been observed that engineering students do not always get the opportunity to interact with a diverse student population (Blouin, 2022), and also the coursework is primarily technical (Lucietto & Russell, 2020). The technical nature of the coursework helps students to develop hard skills, but provides less opportunities to develop professional skills (Bahrami et al, 2023;Jaiswal et al, 2021aJaiswal et al, , 2023aMagana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%